Dysfunction of Endoplasmic Reticulum (ER) and Mitochondria (MT) in Alzheimer's Disease: The Role of the ER-MT Cross-Talk - Volgyi, Katalin; Juhasz, Gabor; Kovacs, Zsolt; Penke, Botond (Current Alzheimer Research, 2015)
A common feature of neurodegenerative diseases is the formation of misfolded, mostly enzyme resistant proteins. These substances may form toxic assemblies according to the current concept of the neurodegenerative diseases. Overlapping of the misfolded proteins is typical in these disorders. The formation of misfolded proteins and toxic aggregates point to a common pathway of these disorders: failure in normal protein folding in the ER as a consequence of ER-stress and mitochondrial energy production. Alzheimer's disease (AD) is a rather heterogeneous, multifactorial disorder with wide clinical heterogeneity and is classified into several subtypes. In AD the processing of the amyloid precursor protein (APP) and formation of toxic β-amyloid (Aβ) structures occur intraneuronally. Aβ affects both ER and mitochondria and disturbs Ca2+-homeostasis of the cells. Mitochondrial dysfunction is one of the main pathological events in AD. Mitochondria accumulate Aβ derived from the ER/Golgi or from the mitochondriaassociated ER-membranes (MAM). Free radicals, oxidative stress and increasing Ca2+-concentration in mitochondria cause decreased ATP production. Mitochondrial dynamic and trafficking are also altered as a result of Aβ toxicity. Synaptic mitochondria show a very high vulnerability. Depletion of Ca2+ level in the ER results in dysfunction of protein folding and evokes unfolded protein response (UPR), and affects also mitochondria. MAM may play special role in the ERmitochondria cross talk. Mitochondria themselves (using mitochondria-targeting antioxidants such as MitoQ) could be a special target for AD treatment. Another targets are the UPR cascade proteins (PERK, IRE1, ATF6) and receptors involved in Ca2+ -level stabilization of the ER (Ryr, IP3R).
Keywords: β-amyloid